Consumer Attitudes And Purchase Intention Towards Eco-Friendly Products: A Regional Study Of Madhya Pradesh (International Journal of Environmental Sciences, 2025)
As environmental sustainability becomes a growing worldwide need, understanding the mental and social components behind eco-friendly buyer behavior is critical, particularly in differing territorial settings like Madhya Pradesh, India. In spite of increased awareness of environmental issues, an outstanding disparity continues between buyer eagerly and genuine eco-friendly purchasing behavior. This study addresses this crevice by looking at five interconnected develops: consumer awareness and knowledge (CAK), attitudes toward eco-friendly products (ATEP), influencing factors, purchase intention (PI), and regional purchase behavior (RPB). Drawing upon behavioral and environmental psychology, a conceptual framework was created and tried utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) on information collected from 207 respondents through an organized overview. The results affirm that CAK altogether improves ATEP, which both ATEP and In case emphatically influence PI. In turn, PI unequivocally predicts RPB, whereas ATEP moreover includes a coordinate impact on RPB, showing both intervened and coordinate pathways. This paper progresses existing models by joining region-specific experiences into eco-conscious consumer behavior. Essentially, the discoveries give significant direction for policymakers and marketers to create focused on interventions and awareness methodologies to drive the adoption of sustainable products in semi-urban Indian markets.